Aspects of indices determination of the children’s pcyhological readiness to the school education - Kuta, Oksana; Malynovych, Larysa (Lviv Polytechnic Publishing House, 2016)
This article includes the main objective of comprehensive psycho diagnostic examination of children with violations of ear to the studies at school, which is general level of psychophysical development of deaf and partially deaf children under school age, their potential and individual peculiarities of development; there has been posed a problem, which is to analyse theoretically aspects of preparation of children for studies at school indices. Result of this analysis is indication of three main aspects of forming the psychological readiness to the school education (the Organizational and Methodical aspect, the Technological aspect and the Improvement and Development aspect) and there has been also specified the issues of this methods’ realization within the modern pre-school education system, indicated variety of educational institutions (conventional, compensatory) for this category of children.
Keywords: psychological readiness to the studies; psychophysical development; deaf; partially deaf; psycho diagnostics; pantomime; Education and Rehabilitation Center